PREDICTION OF THE BIOCORROSION PROCESS AND ITS EFFECT ON THE STRENGTH OF THE MATERIAL - Mawaddatus Sholekhah, Dewi
Biodiesel is an alternative fuel that is more environmentally friendly. Biodiesel is used in Indonesia with a composition of 30%-v biodiesel and 70%-v diesel (B30). However, biodiesel has disadvantages, such as hygroscopic and easily degraded. This causes the occurance of corrosion by microorganisms called biocorrosion or Microbiologically Influenced Corrosion (MIC). This MIC can cause damage to carbon steel as a biodiesel storage material. This research aims to understand the effect of MIC due to B30 culture activity on the strength of carbon steel material. The carbon steel ST 37 and microorganisms in the form of mixed culture of B30 biofilm and culture of B30 mud dilution will be used in this research. The corrosion rate value obtained by using gravimetric method and potentiodynamic polarization. Results showed that the corrosion rate is higher in conditions where microorganisms are growing, especially the B30 sludge dilution culture due to the presence of Pseudomonas sp. which can coexist with sulfate reducing bacteria whose mechanism can accelerate corrosion. The corrosion rate value in the potentiodynamic polarization method is higher than in the gravimetric method due to differences in water accumulation used. When viewed from the value of the corrosion rate to the carbon steel material, carbon steel has a very good relative strength because the corrosion rate in the B30 storage system with and without microorganisms is very low so that the estimated tank damage time is estimated to be very long.